Fruit over sunbed: Carotenoid skin colouration is found more attractive than melanin colouration. Issue 2 (February 2015) - Lefevre, Carmen E.; Perrett, David I.
Skin colouration appears to play a pivotal part in facial attractiveness. Skin yellowness contributes to an attractive appearance and is influenced both by dietary carotenoids and by melanin. While both increased carotenoid colouration and increased melanin colouration enhance apparent health in Caucasian faces by increasing skin yellowness, it remains unclear, firstly, whether both pigments contribute to attractiveness judgements, secondly, whether one pigment is clearly preferred over the other, and thirdly, whether these effects depend on the sex of the face. Here, in three studies, we examine these questions using controlled facial stimuli transformed to be either high or low in (a) carotenoid colouration, or (b) melanin colouration. We show, firstly, that both increased carotenoid colouration and increased melanin colouration are found attractive compared to lower levels of these pigments. Secondly, we show that carotenoid colouration is consistently preferred over melanin colouration when levels of colouration are matched. In addition, we find an effect of the sex of stimuli with stronger preferences for carotenoids over melanin in female compared to male faces, irrespective of the sex of the observer. These results are interpreted as reflecting preferences for sex-typical skin colouration: men have darker skin than women and high melanization in male faces may further enhance this masculine trait, thus carotenoid colouration is not less desirable, but melanin colouration is relatively more desirable in males compared to females. Taken together, our findings provide further support for a carotenoid-linked health-signalling system that is highly important in mate choice.